Exploring Spatiotemporal Changes in Ecosystem Service Values and Hot Spots in Xishuangbanna, Southwestern China - Zhuoya Zhang , Zheneng Hu, Jiaxi Li , Yuze Zhu, Xin Yang (Forest Chemicals Review, 2022)
Xishuangbanna, on the southwestern border of China, is located in the upper reaches of the Mekong River between the Indo-China Peninsula and the East Asian continent. It is the largest tropical rain forest and monsoon forest in China. These forests have an irreplaceable ecological service function, and are an important barrier to maintaining the ecological security of the Mekong River transboundary basin of the Lancang River. We based this study on four sets of remote sensing data (1996, 2003, 2010 and 2016), and explored the spatiotemporal changes inXishuangbanna. We also made an assessment of the different ecosystem values of six types of ecosystem in Xishuangbanna, based on related theories of ecological economics. Results showed that thevalues of its ecosystem services (ES) in 1996, 2003, 2010 and 2016 were 70.4014 billion yuan, 70.2115 billion yuan, 68.5129 billion yuan and 63.6098 billion yuan, respectively. The total value shows a continuously decreasing trend, reflecting the continuous decline in the ability of the ecosystem to provide services to humans. If divided by types, forest and rubber ecosystems supplied the greatest proportion of service values. From the perspective of service types, soil formation and protection accounted for the largest proportion, followed by gas regulation and biodiversity protection. It was useful to study the ES value (ESV) when exploring the sustainable development of resources and economy.